PENGARUH RASIO PROFITABILITAS, LEVERAGE, DAN RASIO PASAR TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hanafi, 09.05.51.0043; Irsyad, Moch. (Students Journal of Economic and Management, 2013)
Basically every investor that invests so expect to benefit from these investments in the future. The advantage is a compensation for the time and risk associated with the investment in doing. Purpose ofinvesting is to maximize investor return, without forgetting the risk factors they face. Before investing, prospective investors would require information relating to the implementation of the investment. Analysis offinancial ratios include profitability ratios, leverage and market ratios. Research on the relationship return on assets (ROA) and stock returns by Sunarto (2001) and Ulupui (2004) which states that the return on assets(ROA) significantly affect stock returns. And, research on the relationship return on equity (ROE) for stock returns by Sunarto (2001) showed that the ROE has a significant effect on stock returns. Meanwhile, researchby Iswadi (2010) showed that the ROE does not significantly affect stock returns. This study population is a manufacturing company whose shares are actively traded during 2008 to 2010. Sample selection techniques conducted by purposive sampling to obtain a sample size 81 issuers. Analysis of the data used to answer the research hypotheses used multiple regression analysis tool, having previously tested the normality of the data and the classical assumptions. In addition, this study also tested the fit of the model. Test equipment is conducted by the F test and the coefficient of determination. The results of this study indicate that the Return on Assets, Earning Per Share, Price Book Value has positive and significant impact on Stock Return; Debt Equity Ratio, Debt To Total Assets negative and significant impact on Stock Return, and Return On Equity had no significant effect Stock Return .Keywords: Return on Assets, Return on Equity, Debt Equity Ratio, Debt To Total Assets Earning Per Share, Price Book Value, and Return of Shares